Analytical modelling strategy for predicting the NSM FRP strips contribution for RC beams shear strength - Bianco, V. (2008)
Shear strengthening of RC beams by means of FRP strips glued by a structural adhesive into thin shallow slits cut in the cover of the web lateral faces, is becoming a popular technique. Nonetheless, many aspects related to the mechanical behaviour and relevant failure modes still need to be clarified. A recent experimental-analytical investigation has demonstrated that, besides debonding and tensile rupture of the strip, the semi-conical tensile fracture of concrete surrounding the strip should be considered among the possible failure modes. A comprehensive analytical model for predicting the NSM strips contribution to the shear strength of RC beams was also developed. Despite its consistency with experimental results, that model had room for improvements. The upgraded version of that analytical model is herein presented and appraised on the basis of some among the most recent experimental results. This appraisal shows the high level of accuracy and potentialities of that modelling strategy arise.